A novel approach of tongue cancer diagnostic imaging: a literature review - Dwiputri, Gavrila Samitra; Rahman, Fadhlil Ulum Abdul (Jurnal Radiologi Dentomaksilofasial Indonesia (JRDI), 2024)
Objectives: This review article is aimed to provide a scientific information about novel approach of tongue cancer diagnostic imaging based on evidence-based reputed published studies. Review: The databases used in this literature review are Google Scholar, PubMed and Elsevier. The research results were selected by title and abstract according to their relevance to the review topic, then the results were selected again based on the inclusion and exclusion criteria. A total of 13 literatures were reviewed. This review shows the diagnostic imaging is a useful tool for staging and management planning in tongue cancers. In this era of technological development, a novel diagnostic imaging technologies that can be used for the diagnosis of tongue cancers such us Ultra High-Frequency Ultrasound (UHFUS), Diffusion-Weighted Imaging MRI (DWI-MRI), Dynamic Contrast-Enhanced MRI (DCE-MRI), Optical Coherence Tomography (OCT), Positron Emission Tomography (PET), Endoscopic images, and the other noninvasive imaging methods like vital staining, autofluorescence, Narrow-Band Imaging (NBI), and in vivo confocal microscopy. Besides that, imaging of tongue cancer requires a multimodality imaging approach to obtain accurate information about pathological condition such as PET/MRI, FDG PET/CT, and SPECT-CT. Conclusion: Each diagnostic imaging has limitations in imaging the patient's condition, so it can be used alone or in combination with one another to obtain accurate information about pathological conditions. FGD PET-CT and UHFUS reportedly provide a high level of sensitivity and specificity to diagnose and staging of tongue cancer.